Structure, stability and bonding of ternary transition metal nitrides - Matenoglou, G. M.; Koutsokeras, Loukas E.; Lekka, Christina E.; Abadias, Gregory; Kosmidis, C.; Evangelakis, Georgios Antomiou; Patsalas, Panos A. (My University, 2009)
Ternary transition metal nitrides have gained special attention in an effort to improve further the properties of the corresponding binary compounds. In this work, we present a comparative study of a very wide range of ternary transition metal nitrides of the form: TixMe1-xN and TaxMe1-xN (Me = Ti,Zr,Hf,Nb,Ta,Mo,W) over the whole x range (0 < x < 1) grown by Pulsed Laser Deposition (PLD) and by Dual Ion Beam Sputtering. We study the stability of the rocksalt structure in all these films experimentally and theoretically through ab-initio calculations. We investigate the validity of Vegard's rule and the effect of growth-dependent stresses to the lattice constant
Keywords: Ternary nitrides; Structure; Bonding; Stress; X-Ray diffraction; ab initio calculations